Efektivitas Penggunaan Metode Eksperimen dalam Meningkatkan Kemampuan Mengenal Warna di Kelas B RA NW Rensing Bat - Susanti, Yuliana (Lembaga Yasin AlSys, 2022)
This study aims to improve the ability to recognize colors by using experimental methods. Children basically like to do new things and learn something interesting, namely by experimenting or experimenting, especially at the level of early childhood whose curiosity is very high. This research is a Classroom Action Research (CAR) using qualitative methods. The research data were obtained by using observation, interview and documentation techniques. The increase in the color recognition of students is marked by the increasing number of positive columns filled in for each indicator set. The research obtained is (1) the indicator of